Socialization of The Danger of Drug Abuse and The P4GN Movement - Andini, Orin Gusta; Alfarisi, Salman; Tiarahman, Adit; Arifurrahman, Arifurrahman; Audrey, Nadya (Universitas Negeri Semarang, 2023)
The aim of the activity to socialize the dangers of drug abuse at Wahidiyah Samarinda Junior High School (SMP) is so that participants can understand the impacts of drug use, both physical, psychological and socio-economic impacts, and what the P4GN Movement is. Socialization activities use participatory methods, lectures and questions and answers. The socialization activity was carried out on July 11 2023 with the number of participants taking part in the socialization activity consisting of 45 students and 2 teachers located in the Wahidiyah Samarinda Middle School hall. For this reason, through this socialization activity on the dangers of drug abuse, it is hoped that it will be able to increase the understanding of Wahidiyah Samarinda Middle School students regarding the types of narcotics that are usually used by teenagers, the impact of narcotics abuse from physical, psychological, educational, social and economic aspects, the P4GN program, as well as ways to prevent and control drug abuse among teenagers.